Non-Timber Forest Products in Phytomedicine and Culinary Uses (2005)
This paper is focused on medicinal and culinary uses of non-timber forest products. A medicinal plant is any plant which one or more of its organs contain(s) substances that can be used for therapeutic purposes or which are precursors for the synthesis of useful drugs. Culinary' plants on the other hand are those plants or products thereof used to flavour foods or beverages before, during or after their preparation. There is no clear distinction between spices and condiments. In the same vein, the distinction between food and medicinal plant is not clear-cut as many edible plants are also used in traditional medicine. Examples of these include: Vernonia amygdalina; Pterocarpus spp. Vitex doniana, Gongoronema laitfolium, Ocimum gratissimum, Crassocephalum rubens; Xylopia aethiopica; Piper guineense and Lactuca taraxacifolia. An attempt is made here to present information on some common medicinal plants with emphasis on their common, scientific and family names; ailment(s) they are used to treat, part(s) of plant used and the relevant authority. Culinary plants including spices and aromatics and the problems militating against the sustainable utilization of these valuable products are discussed while possible conservation methods are proposed.